Genetic diversity of porcine group A rotavirus strains in the UK - Chandler-Bostock, Rebecca; Hancox, Laura R.; Nawaz, Sameena; Watts, Oliver; Iturriza-Gomara, Miren; Mellits, Kenneth M. (Elsevier, 2014)
Rotavirus is endemic in pig farms where it causes a loss in production. This study is the first to characterise porcine rotavirus circulating in UK pigs. Samples from diarrheic pigs with rotavirus enteritis obtained between 2010 and 2012 were genotyped in order to determine the diversity of group A rotavirus (GARV) in UK pigs. A wide range of rotavirus genotypes were identified in UK pigs: six G types (VP7); G2, G3, G4, G5, G9 and G11 and six P types (VP4); P[6], P[7], P[8], P[13], P[23], and P[32]. With the exception of a single P[8] isolate, there was less than 95% nucleotide identity between sequences from this study and any available rotavirus sequences.